Sustainability performance as a governance mechanism: The moderating role in accounting conservatism and tax avoidance in Indonesia - Naila Hanum; Raden Roro Diana Atika Ghozali; Rissa Anandita; Gabrielle J. Salma Silalahi (Proceeding International Conference on Accounting and Finance, 2026)
This study examines the role of Environmental, Social, and Governance (ESG) performance in moderating the relationship between accounting conservatism and tax avoidance among Indonesian listed firms. Using firm-level financial and ESG data obtained from Bloomberg, the analysis was conducted with Stata 17 employing multiple regression and standard diagnostic tests, including heteroskedasticity and multicollinearity assessments. The findings reveal that accounting conservatism does not have a significant direct effect on tax avoidance, indicating that conservative reporting alone does not sufficiently influence firms’ tax strategies. However, ESG performance significantly moderates the association between conservatism and tax avoidance, thereby functioning as a quasi moderator. This suggests that the effectiveness of accounting conservatism in shaping ethical tax behavior becomes meaningful only when firms exhibit strong ESG practices. High ESG performance reinforces transparency, ethical conduct, and stakeholder accountability, which in turn conditions how conservatism influences tax-related decisions. The results contribute to the growing literature on sustainability-oriented governance by providing evidence from an emerging market context. The study highlights the importance of integrating ESG into corporate governance structures, as ESG practices not only enhance reporting credibility but also strengthen firms’ commitment to responsible tax behavior. These findings offer practical implications for regulators, policymakers, and firms seeking to align financial reporting with ethical and sustainable governance standards.